Healthy at last : a plant-based approach to preventing and reversing diabetes and other chronic illnesses - Adams, Eric (Hay House, Inc., 2020)
"Brooklyn Borough President and mayoral candidate Eric Adams is on a mission to tackle one of the most stubborn health problems in the country: chronic disease in the African American community. African Americans are heavier and sicker than any other group in the U.S., with nearly half of all black adults suffering from some form of cardiovascular disease. After Adams woke up with severe vision loss one day in 2016, he learned that he was one of the nearly 5 million black people living with diabetes-and, according to his doctor, he would have it for the rest of his life. A police officer for more than two decades, Adams was a connoisseur of the fast-food dollar menu. Like so many Americans with stressful jobs, the last thing he wanted to think about was eating healthfully. Fast food was easy, cheap, and comfortable. His diet followed him from the squad car to the state senate, and then to Brooklyn Borough Hall, where it finally caught up with him"--